Glycemic and insulinemic responses to resistant starch type 4 - Steele, Trevor Jordan (Kansas State University, 2021)
The overall aim of this dissertation was to determine the effects of resistant starch type 4 (RS4) on postprandial glycemic and insulinemic responses, and to determine whether there were differences between United States Food and Drug Administration (FDA) approved testing methods (add-on or substitution, with matched digestible carbohydrate amounts) and non-FDA approved testing methods (substitution without matched digestible carbohydrate amounts). The first study (Chapter 2) examined the impact of RS4 consumption on glycemic and insulinemic responses using the FDA approved add-on method, a method of adding the fiber on top of the control treatment, and the non-FDA approved substitution method, a substitution method used for manufacturing products available to consumers. We used a randomized controlled crossover design to compare postprandial glycemic and insulinemic responses following consumption of RS4 crackers and native wheat starch (NWS) crackers. The results indicated that insulin incremental area under the curve (iAUC) was significantly lower (~87%) following consumption of RS4 crackers compared with NWS crackers manufactured using the non-FDA approved substitution method. However, no differences were observed in glycemic or insulinemic responses following consumption of RS4 or NWS crackers manufactured using the FDA approved add-on method (ps>0.05). These findings suggest that the FDA approved add-on method and non-FDA approved substitution method should be further investigated to elucidate the importance of the differences between the way ingredients are tested versus how they are packaged, purchased, and used by consumers. Therefore, the second study (Chapter 3) utilized the FDA approved substitution method where RS4 was substituted in place of a carbohydrate containing ingredient (puffed wheat) in the control treatment. Using a randomized controlled crossover design, we investigated the postprandial glycemic and insulinemic responses following consumption of RS4 nutrition bars and puffed wheat bars (PWB) across two doses of digestible carbohydrate, one more typical of FDA testing, and one more typical of how products are manufactured, packaged, and purchased by consumers. This study revealed that glucose and insulin iAUC were significantly lower in the 30g digestible carbohydrate conditions compared to the 50g digestible carbohydrate conditions (p<0.05) and were also significantly lower in RS4 conditions compared with PWB and dextrose conditions (ps<0.05). Results for the RS4 nutrition bars indicated a mean reduction of ~50% for glucose iAUC and a mean reduction of ~46% for insulin iAUC compared with the PWB and dextrose conditions. These findings suggest that RS4 produces beneficial glycemic and insulinemic responses, regardless of the dose of digestible carbohydrate. To further investigate the effects of RS4 on glycemic and insulinemic responses using the FDA approved and non-FDA approved testing methods, Chapter 4 reports the results of a systematic review and meta-analysis of human randomized clinical trials investigating the effects of RS4 on postprandial glucose and insulin iAUC. The meta-analysis indicated that RS4 significantly reduces postprandial glucose and insulin iAUC compared to control conditions. Further, a subgroup analysis confirmed that glucose iAUC was significantly lower compared with control condition across both FDA approved and non-FDA approved testing methods. However, in studies that used FDA approved substitution methods, insulin iAUC was not different between RS4 and control conditions, whereas there were significant reductions in insulin iAUC following RS4 consumption observed in studies using the non-FDA approved substitution method. These collective findings indicate an overall reduction in postprandial glycemic and insulinemic responses following RS4 consumption when compared to control conditions, consistent with the current literature. However, the beneficial responses are more consistent when utilizing digestible carbohydrate amounts and testing methods typical of products that can be purchased by consumers. Overall, the studies included in this dissertation suggest beneficial metabolic effects following RS4 consumption and indicate a need for further investigation of the use of RS4 in product development. Substitution of RS4 in carbohydrate containing products may be a potentially feasible approach for helping to mitigate the increasing burden of non-communicable chronic diseases, metabolic diseases in particular.
Keywords: Resistant starch; Resistant starch type 4; Postprandial glucose; Postprandial insulin